Low Frequency Electromagnetic Fields: Friend or Foe? - Ivo Cap; Jan Barabas (Communications - Scientific letters of the University of Zilina, 2011)
The issue of electromagnetic fields and their effects on human health has long been discussed within the scientific community. The lack of undisputable evidence confirming the dangers of these fields leads to great uncertainty and public concerns. On the other hand, positive effects and possible therapeutic use of the mentioned fields has also been explored and currently hints at feasible application thereof in regenerative and therapeutic applications. The following article provides a balanced insight into the issue at hand and provides details of recently proposed mechanisms of actions.